CLUSTER ANALYSIS TO CLASSIFY THE LEVEL OF SOCIAL WELFARE OF THE COMMUNITY IN DELI SERDANG REGENCY USING FUZZY C-MEAN CLUSTERING DURING THE COVID-19 PANDEMIC - Salasa Riana, Dwi; Rakhmawati, Fibri; Widyasari, Rina (Pena Cendekia Insani, 2022)
The Covid-19 pandemic has greatly affected the social welfare of the affected communities in each region. Based on data sources that there are many people who have lost their jobs and lack of income, the government provides a number of assistances to help people affected by covid-19. This study uses data on the number of reciptients of cash social assistance (BST) in Deli Serdang Regency in 2020 which aims to look at the problems of assistance received by the community towards the social welfare of the community. This study uses fuzzy c-mean clustering method because social welfare groupings can be grouped appropriately. Based on the results of fuzzy c-mean clustering analysis will produce three clusters that have different characteristics. The sub-district included in cluster 1, namely Hamparan Perak, Percut Sei Tuan, Sunggal, Tanjung Morawa are sub-districs that have a low level of welfare during the covid-19 pandemic because in these sub-districs the population is more than other sub-districs. Located in Deli Serdang regency.